An Individualistic Homoeopathic Approach in a Case of Infected Epidermal Naevus—A Case Report - Das, Torsa (Homœopathic Links, 2024)
Naevi are circumscribed developmental defects or the lack of one or more components of the skin that manifest as overgrowths or hamartomas derived from embryonic ectoderm. The majority of naevi are present at birth or appear soon after birth. Naevi can be infected by various organisms, particularly by Staphylococcus, without other systemic involvement, similar to the skin. A 30-year-old male patient presented with an infected, painful congenital epidermal naevus on the anterior side of his right thigh. He experienced severe itching, burning, and sudden blister formation. After treatment, the infection completely resolved, leaving the naevus without any complications. Possible causal attribution of these changes was determined using the Modified Naranjo Criteria (score: 8 out of 13). No recurrence of further infection was reported in the next year, demonstrating the positive curative role of individualized homeopathic treatment in a case of infected epidermal naevus.
Keywords: infected naevi; individualisation; homoeopathy; Sulphur